Effects of two chronic stress models on ligature-induced periodontitis in Wistar rats - Semenoff-Segundo, Alex; Porto, Alessandra Nogueira; Dele Vedove Semenoff, Tereza Aparecida; Cortelli, Jose Roberto; Costa, Fernando Oliveira; Cortelli, Sheila Cavalca; Bosco, Álvaro Francisco [UNESP] (Pergamon-Elsevier B.V. Ltd, 2012)
Objectives: The present study aims at comparing the effects of physical and variable chronic stress on ligature-induced periodontitis in rats.Design: Forty-eight adult Wistar rats were randomly assigned to four groups (n = 12): physical stress, variable stress, positive control and negative control. The models of physical stress were immobilization and immobilization associated with exposure to cold. The models of variable stress were exposure to intermittent light, 24 h isolation, oral cavity examination, crowded environment, smell of blood and noise. After 10 days of physical or variable stress animals underwent experimental induction of periodontal disease in one oral side. Positive control also underwent experimental induction of periodontal disease on the 10th day. Negative control did not receive any type of intervention. At the end of the experimental period (60 days), all animals were euthanized. After routine laboratory processing, images of the histological sections were digitised and submitted to histometric measurement using two parameters: histologic attachment loss and bone loss.Results: Histological attachment loss and bone loss were greater (p < 0.05) in the physical stress group than in the other groups (variable stress, positive and negative control groups). on the non-periodontitis side, these same histological parameters did not significantly differ amongst groups.Conclusions: Physical stress negatively modulated the response pattern to experimentally induced periodontitis in rats. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Stress; Physiological; Rats; Periodontitis